(untitled) (The Review of Diabetic Studies, 2025)
Emergency medical services (EMS) are a key component of contemporary healthcare systems, especially in the management of life-threatening and time-sensitive conditions. The effectiveness of such services not only depends on the quality of care that is delivered within hospitals, but also on the effectiveness of pre-hospital interventions, during which ambulance services can be used as the first point of contact with patients. Here, ambulance preparedness becomes a crucial determinant that directly impacts the timeliness and success of emergency response and patient outcomes. Ambulance preparedness is not simply a question of vehicle availability, it is a demonstration of the overall level of preparedness which includes the sufficiency of the medical equipment, the dependability and maintenance of ambulances and the competency of the emergency staff. Well equipped ambulance system guarantees quick responses to emergencies, appropriate onsite treatment, and safe transportation of patient to healthcare facilities. Conversely, any shortage in preparedness like delay in response time or inadequate relevant resources could adversely impact patient conditions and exert further pressure on hospital emergency departments.